Global stability analysis for SEIS models with n latent classes - Napoleon Bame; Samuel Bowong; Josepha Mbang; Gauthier Sallet; Jean-Jules Tewa (Mathematical Biosciences and Engineering)
We compute the basic reproduction ratio of a SEIS model withn classes of latent individuals and bilinear incidence.The system exhibits thetraditional behaviour. We prove that if R0 ≤1, then the disease-free equilibriumis globally asymptotically stable on the nonnegative orthant and ifR0 > 1, an endemic equilibrium exists and is globally asymptotically stableon the positive orthant.